2009
DOI: 10.1128/iai.01205-08
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenesσBModulates PrfA-Mediated Virulence Factor Expression

Abstract: Listeria monocytogenes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(154 citation statements)
references
References 78 publications
12
141
1
Order By: Relevance
“…opuCC (i) is also preceded by a putative s B -dependent promoter and (ii) belongs to the four-gene opuC operon that has been identified in (Fraser et al, 2003;Sue et al, 2003). lmo0265, which had a significant P c value and a FC of 8.0 reported in the Oliver et al (2010) microarray study, did not show evidence for differential expression in the two other array studies (Ollinger et al, 2009;Raengpradub et al, 2008), which used an EGD-e array that had an lmo0265 probe with low (71 %) homology to the 10403S lmo0265 gene, likely leading to a false-negative result in these two studies.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…opuCC (i) is also preceded by a putative s B -dependent promoter and (ii) belongs to the four-gene opuC operon that has been identified in (Fraser et al, 2003;Sue et al, 2003). lmo0265, which had a significant P c value and a FC of 8.0 reported in the Oliver et al (2010) microarray study, did not show evidence for differential expression in the two other array studies (Ollinger et al, 2009;Raengpradub et al, 2008), which used an EGD-e array that had an lmo0265 probe with low (71 %) homology to the 10403S lmo0265 gene, likely leading to a false-negative result in these two studies.…”
Section: Resultsmentioning
confidence: 82%
“…A meta-analysis of three published microarray studies was performed to identify genes that showed differential transcript levels between the L. monocytogenes parent strain 10403S and an isogenic DsigB strain. Two of these studies used 10403S and an isogenic DsigB strain (Oliver et al, 2010;Raengpradub et al, 2008), while one study (Ollinger et al, 2009) used an L. monocytogenes 10403S prfA* strain, which constitutively expresses an active form of the virulence gene transcriptional activator PrfA, and an isogenic prfA*DsigB strain. Two of these studies (Ollinger et al, 2009;Raengpradub et al, 2008) used the same set of microarray probes, which were designed based on the genome sequence of strain EGD-e, while the other study (Oliver et al, 2010) used a set of microarray probes designed based on four different genomes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…188 It is interesting to note that a significant subset of PrfA-regulated genes have potential σ B promoter sequences. 180 In addition, recent evidence has arisen suggesting that σ B fine-tunes prfA expression inside host cells to avoid overexpression of virulence genes, 189 which could result in excessive host cell damage and thus impair the success of bacteria in establishing infection. This finding highlights the overlap that exists between the control of the general stress response and the control of virulence-related functions.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%